Safe but Lonely? Loneliness, Anxiety, and Depression Symptoms and COVID-19 - Okruszek, Łukasz; Aniszewska-Stańczuk, Aleksandra; Piejka, Aleksandra; Wiśniewska, Marcelina; Żurek, Karolina (Frontiers in Psychology, 2020)
The COVID-19 pandemic has led governments worldwide to implement unprecedented response strategies. While crucial to limiting the spread of the virus, “social distancing” may lead to severe psychological consequences, especially in lonely individuals. Methods: We used cross-sectional (n=380) and longitudinal (n=74) designs to investigate the links between loneliness, anxiety and depression symptoms (ADS) and COVID-19 risk perception and affective response in young adults who implemented social distancing during the first two weeks of the state of epidemic threat in Poland. Results: Loneliness was correlated with ADS and with affective response to COVID-19’s threat to health. However, increased worry about the social isolation and heightened risk perception for financial problems was observed in lonelier individuals. The cross-lagged influence of the initial affective response to COVID-19 on subsequent levels of loneliness was also found. Conclusions: Thus, the reciprocal connections between loneliness and COVID-19 response may be of crucial importance for ADS during COVID-19 crisis.